Opportunistic Non-Orthogonal Random Access With Optimal Decoder for 6G Multi-Channel IoT Networks - Yeom, Jeong Seon; Jung, Bang Chul (IEEE Wireless Communications Letters, 2025)
A novel opportunistic non-orthogonal random access (O-NORA) technique is proposed for multi-channel systems in sixth-generation (6G) massive connection scenarios, such as Internet of Things (IoT) networks. In this letter, K IoT devices (IDs) independently transmit their packets to a single access point (AP) over one of M available channels. To meet the low-complexity requirements of IoT applications, all nodes are assumed to operate with a single antenna. Specifically, the optimal simultaneous non-unique decoding (SND) technique is leveraged at the AP to enhance network reliability. A rigorous mathematical analysis of the outage probability and channel utilization for the proposed O-NORA technique is provided. The accuracy of our analytical results is validated through simulations. The proposed O-NORA with SND demonstrates a significant performance gain over conventional schemes in terms of outage probability and throughput for 6G multi-channel uplink IoT networks.
Keywords: 6g mobile communication; Massive internet of thing network; Mobile communications; Multi channel; Non-orthogonal; Non-orthogonal random access; Opportunistic transmission; Outage probability; Random access; Simultaneous non-unique decoding; 6G mobile communications; massive IoT networks; non-orthogonal random access; opportunistic transmission; outage probability; simultaneous non-unique decoding